2019
DOI: 10.1111/epi.16402
|View full text |Cite
|
Sign up to set email alerts
|

External validation and comparison of two prediction models for seizure recurrence after the withdrawal of antiepileptic drugs in adult patients

Abstract: Objective:The models currently available for predicting the risk of seizure recurrence after antiepileptic drug (AED) withdrawal in adult epilepsy patients include the prediction model developed by Lamberink et al (Lamberink model, 2017) and the Medical Research Council prediction model (MRC model, 1993). However, there was no external validation for the two models. The purpose of this study was to perform an independent external validation and a comparison of the Lamberink model and the MRC model in adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…The calculator for the risk of withdrawal is available at https://tinyurl.com/uxyu26p, which can be used to evaluate the 2year and 5-year recurrence risks after withdrawal and quantify the probability of achieving a seizure-free status at 10 years after withdrawal. In 2019, Lin et al [94] used a database to validate the prediction models proposed by Lamberink et al [33] and the MRC [88] with a cohort of 212 patients in all age groups who withdrew from AEDs and underwent long-term follow-up. The areas under the curves (AUCs) were 0.71 and 0.68 for the 2-year and 5-year models proposed by Lamberink et al, while AUCs were 0.60 and 0.58 for the 1-year and 2-year models from the MRC, respectively.…”
Section: Patients Receiving Aeds Alonementioning
confidence: 99%
See 1 more Smart Citation
“…The calculator for the risk of withdrawal is available at https://tinyurl.com/uxyu26p, which can be used to evaluate the 2year and 5-year recurrence risks after withdrawal and quantify the probability of achieving a seizure-free status at 10 years after withdrawal. In 2019, Lin et al [94] used a database to validate the prediction models proposed by Lamberink et al [33] and the MRC [88] with a cohort of 212 patients in all age groups who withdrew from AEDs and underwent long-term follow-up. The areas under the curves (AUCs) were 0.71 and 0.68 for the 2-year and 5-year models proposed by Lamberink et al, while AUCs were 0.60 and 0.58 for the 1-year and 2-year models from the MRC, respectively.…”
Section: Patients Receiving Aeds Alonementioning
confidence: 99%
“…Current models for predicting the recurrence risk after withdrawal are accurate and convenient references; however, most models are only applicable to specific populations with epilepsy, and different variables are used to predict the recurrence risk after withdrawal in different patient populations. To date, only a few external validation studies have been conducted to independently validate the usefulness and accuracy of these prediction models [94]. In addition, no consensus has been established for withdrawal in patients with acute symptomatic epilepsy, and no predictive variables or models have been developed to predict the recurrence risk after AED withdrawal in these patients.…”
Section: Expectationsmentioning
confidence: 99%
“…Thus, neurologists can provide their patients with well‐reasonable data on an issue with a high impact in their lives. The results of Lamberink et al 8 for the 2‐year follow‐up have recently been confirmed in an independent cohort of patients 9 . An important limitation of the Lamberink model is that the risk of seizure relapse of patients staying on ASM could not be compared with the risk of those who were discontinued.…”
Section: Recurrence Risk In Seizure‐free Patients Withdrawing Antiseimentioning
confidence: 88%
“…A major obstacle to the practical implementation of LPM is represented by the lack of a single threshold probability value that separates high‐risk from low‐risk patients. Lin et al tried to overcome this issue by a decision curve analysis: This method, unfortunately, did not offer a specific cut‐off but it revealed that the model's usefulness resides in a specific probability range 20 . On the contrary, Chu et al proposed a cut‐off by calculating the largest Youden index on receiver‐operating characteristic (ROC) curves: at 2 years this value was 47% (with a sensitivity of 0.758 and a specificity of 0.410), whereas at 5 years it was 77% (sensitivity of 0.358 and a specificity of 0.979) 21 .…”
Section: Discussionmentioning
confidence: 99%